Outcome of Epilepsy Surgery in Early Childhood - J Gordon Millichap (Pediatric Neurology Briefs, 1999)
The medical records of 23 children, ages 0-3 years, who were treated surgically for epilepsy between 1991 and 1996 were analysed at the Hospital for Sick Children, Toronto, Canada.